Information System for Managing Village-Owned Enterprises (BUMDes) in Bogoharjo Village with DevOps Method - Buchori, Achmad; Muthoharoh, Nurul Afifah; Wijayanto (Scientific Journal of Informatics, 2024)
Purpose: The purpose of this research is to build a Bogoharjo Village-Owned Enterprises (BUMDes) Business Unit Management Information System to facilitate BUMDes managers in managing business units and providing available services to the community online. Methods: The method used in this research is the DevOps method with the stages of plan, code, build, test, release, deploy, operate, and monitor. System design uses UML (Unifed Modeling Language), namely flowchart, use case diagram, activity diagram, class diagram, and sequence diagram. System development using the Laravel framework. Results: The results showed that expert validation with an average percentage by content expert validation of 89% and media expert validation of 84% so that the BUMDes Management Information System (Village-Owned Enterprises) in Bogoharjo Village with the DevOps Method was very feasible to use. While the results of the practicality trial using 25 respondents produced an average percentage of 89% with a very practical category. Thus, the BUMDes Management Information System (Village-Owned Enterprises) in Bogoharjo Village with the DevOps Method is very practical to use. Novelty: The novelty of this research is used to assist BUMDes managers in managing data or providing information related to the BUMDes itself. In addition, BUMDes management becomes more organized and structured so that services to the community become more effective and well managed.